Life Nurturing in the illustrated daoyin of the 24 solar terms (二十四节气) - Yi Shen (Wolters Kluwer Health/LWW, 2019)
China's "24 Solar Terms", known as the fifth invention after China's Four Major Inventions, is a knowledge system and social practice formed through observations of the sun's annual motion, and cognition of the year's changes in season, climate and phenology. More and more people in the world have been eager to know more about it since UNESCO inscribed China's "24 Solar Terms" on the Representative List of the Intangible Cultural Heritage of Humanity in 2016. As a way of nurturing life, the Illustrated Daoyin of the 24 Solar Terms includes twenty-four exercise forms, corresponding to the 24 solar terms respectively, which reflects the significant idea of complying with the law of yin-yang changes in the universe. It presents a series of sitting and standing exercises designed to prevent diseases that occur during seasonal changes throughout the year. The ancient Chinese wisdom of time and life nurturing has been witnessed in China's "24 Solar Terms" and "Illustrated Daoyin of the 24 Solar Terms". This article aims to arouse readers' concern and interest in life nurturing by introducing how to do all the exercises presented by the Illustrated Daoyin of the 24 Solar Terms, which is helpful to the prevention and cure of diseases as well as good for health.